2013
DOI: 10.1369/0022155413498088
|View full text |Cite
|
Sign up to set email alerts
|

Growth Arrest Specific 1 (GAS1) Is Abundantly Expressed in the Adult Mouse Central Nervous System

Abstract: Growth arrest specific 1 (GAS1) is a pleiotropic protein that induces apoptosis and cell arrest in different tumors, but it is also involved in the development of the nervous system and other tissues and organs. This dual ability is likely caused by its capacity to interact both by inhibiting the intracellular signaling cascade induced by glial cell-line derived neurotrophic factor and by facilitating the activity of the sonic hedgehog pathway. The presence of GAS1 mRNA has been described in adult mouse brain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Furthermore, we confirmed the levels of GAS1 in the rat brain at different ages by ELISA. The expression of GAS1 in rat brain, from postnatal 0 to the adult is similar to that previously described in mouse (Zarco et al 2013;Estudillo et al 2016).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, we confirmed the levels of GAS1 in the rat brain at different ages by ELISA. The expression of GAS1 in rat brain, from postnatal 0 to the adult is similar to that previously described in mouse (Zarco et al 2013;Estudillo et al 2016).…”
Section: Discussionsupporting
confidence: 83%
“…To confirm whether the anti-mouse GAS1 antibody recognizes the same protein in the rat, we performed western blot and ELISA assays using whole rat brain extracts of P0, P7 day-old and adult rats since GAS1 is expressed at the same ages in the mouse (Zarco et al 2013;Estudillo et al 2016). We observed a protein band corresponding to GAS1 (37 kDa) in all brain extracts of the rat as confirmed by the positive control, NIH/3T3 mouse cells at confluence (Fig.…”
Section: Gas1 Is Present In the Cerebrospinal Fluid Of The Adult Ratmentioning
confidence: 99%
“…In contrast, it has been reported that Gas1 may also act as a positive regulator of cell proliferation in mouse cerebellum during development (Liu et al, ); and also is expressed in different types of progenitor cells (Izzi et al, ; Kann et al, ), demonstrating the significant role of Gas1 in embryonic development (Lee et al, 2001; Lee & Fan, ; Martinelli & Fan, ). In fact, we have demonstrated that Gas1 is present in progenitor cells during the development of the dentate gyrus and the cortex (Estudillo, Zavala, Perez‐Sanchez, Ayala‐Sarmiento, & Segovia, ) and also in neurons and astroglial cells of adult mouse brain (Zarco et al, ). Finally, these results indicate that Gas1 may act either as a regulator of cell proliferation or as an inducer of cell death in a finely controlled spatio‐temporal manner.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we reported that Gas1 is mainly found in neurons and in a more restricted manner in glial cells in different regions of the CNS of adult mice. [97] Furthermore, the expression of Gas1 decreases when neural stem cells are differentiated to a glial phenotype. [98] However, the role of Gas1 in glial cells is unknown in the adult CNS.…”
Section: Gas1 Protein Structure and Expressionmentioning
confidence: 99%